Physics for scientists and engineers with modern physics - Serway, Raymond A.; Jewett, John William 1928- (Brooks/Cole Cencage Learning, 2014)
The Analysis Model approach lays out a standard set of situations that appear in most physics problems, and serves as a bridge to help students identify the correct fundamental principle - and then the equation - to utilize in solving that problem